2020
DOI: 10.1074/jbc.ra120.013583
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal oxidation of erucic acid suppresses mitochondrial fatty acid oxidation by stimulating malonyl-CoA formation in the rat liver

Abstract: Feeding of rapeseed (canola) oil with a high erucic acid concentration is known to cause hepatic steatosis in animals. Mitochondrial fatty acid oxidation plays a central role in liver lipid homeostasis, so it is possible that hepatic metabolism of erucic acid might decrease mitochondrial fatty acid oxidation. However, the precise mechanistic relationship between erucic acid levels and mitochondrial fatty acid oxidation is unclear. Using male Sprague–Dawley rats, along with biochemical and molecular biology app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…The abovementioned results were recently supported by Chen et al [108], reporting that feeding animals a diet high in rapeseed oil (rich in erucic acid, a very-long-chain fatty acid) leads to PPARα activation with an adaptive elevation in peroxisomal β-oxidation capacity, which suggested that erucic acid might act as a potential ligand for PPARα. In line with prior communicated data, Maheshwari et al [109] reported that treating rat Fao cells with a fungal lipid extract rich in monomethyl BCFAs (Conidiobolus heterosporous) increases mRNA levels of the PPARα target genes Acox1, Cyp4a1, Cpt1A, and Slc22A5, strongly suggesting that BCFAs are similarly potent PPARα activators [109].…”
Section: Pparα Natural Ligandsmentioning
confidence: 61%
See 2 more Smart Citations
“…The abovementioned results were recently supported by Chen et al [108], reporting that feeding animals a diet high in rapeseed oil (rich in erucic acid, a very-long-chain fatty acid) leads to PPARα activation with an adaptive elevation in peroxisomal β-oxidation capacity, which suggested that erucic acid might act as a potential ligand for PPARα. In line with prior communicated data, Maheshwari et al [109] reported that treating rat Fao cells with a fungal lipid extract rich in monomethyl BCFAs (Conidiobolus heterosporous) increases mRNA levels of the PPARα target genes Acox1, Cyp4a1, Cpt1A, and Slc22A5, strongly suggesting that BCFAs are similarly potent PPARα activators [109].…”
Section: Pparα Natural Ligandsmentioning
confidence: 61%
“…Several peroxisomal β-oxidation substrates display a substantial role as PPARα modulators. It is believed that the activities of (inducible and non-inducible) peroxisomal fatty acid β-oxidation systems are modulated by PPARα [108]. Moreover, several findings provide significant evidence that VLCFA and BCFA, which are considered potentially toxic fatty acids, are potent inducers of PPARα that enhance the transcription of peroxisomal enzymes mediating fatty acid β-oxidation [57,188].…”
Section: Metabolic Regulation Of the Peroxisomal β-Oxidation Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The third and final reaction chosen occurs in peroxisomes, where lactate and NAD+ are converted to pyruvate and NADH by NAD+ oxidoreductase. The pyruvate/lactate ratio is linked with the NAD+/NADH ratio [ 62 ], potentially suggesting that the pyruvate is then shuttled back into the cytosol to be recycled into the citric acid cycle. Following the evidence described above, we set the lower bound of phosphogluconate dehydrogenase, acyl‐CoA oxidase and NAD+ oxidoreductase to 80% of their maximum value.…”
Section: Methodsmentioning
confidence: 99%
“…Peroxisomes play particularly important roles in FAO, ether-phospholipid biosynthesis, and ROS metabolism ( Figure 1 ). Previous studies have shown that β-oxidation of FAs predominantly occurs in mitochondria;, although peroxisomes also participate in FA oxidation ( Chen X. et al, 2020 ; Luppi et al, 2020 ). Although the integral compounds and full-scale function of peroxisomes remain unclear, it has been demonstrated that peroxin (PEX) families are essential components that maintain their structure and function, and peroxisome proliferator-activated receptors (PPARs), a set of three receptor subtypes (PPARα, γ, and δ) regulate a broad range of genes in many metabolically active tissues.…”
Section: Fatty Acid Metabolism and Ferroptosismentioning
confidence: 99%